Pengaruh Sarana Dan Prasarana Terhadap Hasil Belajar Siswa - Gea, Lisda; Harefa, Envilwan Berkat (Jayapangus Press, 2025)
Education is a learning process that aims to develop individual potential optimally, including aspects of knowledge, skills, attitudes and moral values. The success of the educational process is greatly influenced by the availability of facilities and infrastructure, both in schools and universities. Facilities and infrastructure are the main components that support learning activities. The absence of these facilities can hinder the learning process, which ultimately affects student learning outcomes. This research aims to analyze the influence of facilities and infrastructure on student learning outcomes at SMK Negeri 1 Lotu. The research method uses a quantitative approach with a descriptive design. The research subjects were 21 class XII students of the Department of Design, Modeling and Building Information (DPIB). Data was obtained through questionnaires for facilities and infrastructure variables, as well as documentation for learning outcome variables. The data analysis technique uses a simple linear regression formula. The research results show that there is a positive and significant influence between facilities and infrastructure on student learning outcomes. The simple regression equation obtained is Ŷ = 48.329 + 0.425X, meaning that every increase in one unit of facilities and infrastructure increases learning outcomes by 0.425 points. Hypothesis test (tcount = 2.744>ttable=2.074tcount = 2.744 > ttable = 2.074tcount=2.744>ttable=2.074) with a significant value of 0.013 (<0.05) indicating the alternative hypothesis is accepted. The contribution of facilities and infrastructure to student learning outcomes is 28.4%. In conclusion, facilities and infrastructure play an important role in student learning outcomes, but other factors such as teaching quality, motivation and learning environment also need to be considered to achieve optimal learning outcomes.